2007
DOI: 10.1124/jpet.107.123836
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Glycine-Activated Currents in HEK 293 Cells Expressing N-Methyl-D-aspartate NR1 and NR3 Subunits

Abstract: N-Methyl-D-aspartate (NMDA) receptors are important targets for drugs of abuse such as ethanol, toluene, and ketamine. Ligand-gated ion channels assembled from the NR1 and NR3 subunits have functional and pharmacological properties that are distinct from those of conventional NMDA receptors containing NR2 subunits. In the present study we used voltageclamp electrophysiology to characterize excitatory glycine-activated receptors assembled from NR1, NR3A, and NR3B subunits expressed in human embryonic kidney (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 32 publications
(57 reference statements)
5
75
1
2
Order By: Relevance
“…NR3A subunit shows absolute selectivity for glycine over glutamate. These biochemical data corroborated with functional electrophysiological observations that showed glycine alone is sufficient to activate heterologous diheteromeric NR1/NR3 and triheteromeric NR1/ NR3A/NR3B receptors (Chatterton et al, 2002;Smothers and Woodward, 2007) (Fig. 4).…”
Section: Nr3 Ligand Binding Domainsupporting
confidence: 76%
“…NR3A subunit shows absolute selectivity for glycine over glutamate. These biochemical data corroborated with functional electrophysiological observations that showed glycine alone is sufficient to activate heterologous diheteromeric NR1/NR3 and triheteromeric NR1/ NR3A/NR3B receptors (Chatterton et al, 2002;Smothers and Woodward, 2007) (Fig. 4).…”
Section: Nr3 Ligand Binding Domainsupporting
confidence: 76%
“…In contrast, there is evidence that the triheteromeric NR1/NR2/NR3 receptor forms in parietooccipital cortical neurons of P8 mice, based on the observation of single-channel currents with reduced amplitude that were induced by NMDA, were Mg 2ϩ -insensitive, and could be blocked by APV, properties that could not be attributed to either NR1/NR2 or NR1/NR3 receptors (16). In HEK293 cells, upon coexpression of one type of NR3 (NR3A or NR3B) with NR1/NR2, the NMDA-induced Ca 2ϩ permeability of the cells changed and channels with reduced conductance were observed, also supporting the formation of NR1/NR2/NR3 triheteromers because NR1/NR3A or NR1/NR3B receptors do not form in HEK293 cells (12,14,17). It is noteworthy, however, that although coexpression of NR1/ NR2/NR3 appears to consistently result in reduced whole-cell current when compared with expression of NR1/NR2 in both oocytes and HEK 293 cells, Sucher et al (9) failed to detect a change in the Mg 2ϩ sensitivity of NMDA-or glutamate-induced currents in oocytes and Nishi et al (11) failed to do so in HEK 293 cells.…”
mentioning
confidence: 86%
“…Occupancy of the GluN1 subunit by ligand within GluN1/GluN3 receptors seems to facilitate desensitization. In GluN1/GluN3 receptors, GluN3 is activated fully by glycine and partially by D-serine and 1-aminocyclopropane-1-carboxylic acid (Chatterton et al, 2002;Smothers and Woodward, 2007), which may account for observations that D-serine antagonized GluN1/GluN3 receptors (Awobuluyi et al, 2007).…”
Section: Glutamate Receptor Ion Channelsmentioning
confidence: 99%
“…When coexpressed with GluN1 in X. laevis oocytes, GluN1/GluN3 receptors can form receptors that are activated by glycine alone (Chatterton et al, 2002), but these excitatory glycine receptors have not yet been observed in GluN3-expressing neurons (Matsuda et al, 2003). At present, surface expression of glycine-activated GluN1/GluN3A or GluN1/GluN3B receptors in HEK293 cells is unresolved, but GluN1/ GluN3A/GluN3B shows some functional expression (Smothers and Woodward, 2007). When GluN3 is coexpressed with GluN1 and GluN2 in X. laevis oocytes, NMDA-and glutamate-activated current amplitudes are reduced compared with current from GluN1/GluN2, suggesting that either triheteromeric GluN1/GluN2/ GluN3 receptors form that have a lower conductance, or GluN3 expression reduces trafficking or assembly of GluN1/GluN2 (Das et al, 1998;Perez-Otano et al, 2001; Isacoff, 2007, 2008).…”
Section: Identity and Conservation Of Residues In Glutamate Receptor mentioning
confidence: 99%